Entrenched disadvantage and the internationalization of education: A review of the Science without Border Program in Brazil - Barbosa, Rafael Silva; Adefila, Arinola; Garcia , Maria Lúcia Teixeira (Education Policy Analysis Archives, 2022)
Brazil has focused on internationalization of the higher education sector, in response to trends across the globe. The main program for promoting internationalization was the Science without Borders program. The paper analyses Brazilian international mobility from a regional perspective, particularly reviewing how inequality affected access to fellowships. The Northeast Region, which historically records higher poverty indicators than the South and Southeast regions, showed average growth statistically equal to the Southeast Region. By comparing access to scholarships and fellowships between the two largest regions of Brazil, this paper sought to analyze any structural change between the Southeast region and the Northeast. The Science without Borders (Ciência sem Fronteira, in Portuguese) program has achieved considerable results. In the first four years of the program, completed student exchange programs increased by 1,620% (i.e., 2011-2014). Despite this, the structure of unequal regional access remained. Using the hypothesis test methodology T for means with different variances, it was possible to evaluate at a significance level of 95%. The two largest regions in Brazil maintained the unequal profile of access to the program. The conclusion is that the growth in the offer of scholarships for internationalization between 2010 and 2019 has not changed the unequal regional profile of access to public education services in Brazil.